Mothers' Perceptions of the Quality of Postnatal Care Provided in Health Centers and the Associated Factors: A Cross-Sectional Study - Maryam Ahmadinezhad; Fatemeh Vizeshfar; Azadeh Pakniat (Shiraz University of Medical Sciences, 2022)
Background: Postnatal care plays a great role in the health of mothers and their neonates. This study aimed to evaluate the mothers' perceptions of the provided postnatal care and the associated factors. Methods: In this cross-sectional study, the health centers of Sirik city in Hormozgan province, Iran, were selected using convenience sampling. The study was conducted on 160 mothers who had referred to the selected centers for postnatal care from 7 August 2018 to 2 August 2020 and had given birth to live full-term neonates (>37 weeks of gestation) 40 days to 12 months before sampling. The Mothers' Perceptions of the Quality of Postnatal care questionnaire was designed by the research team; it included 18 questions about mothers' perception of care. The collected data were analyzed using the SPSS software, version 21. Results: The mothers' mean score of perception was 69.84±16.04; most mothers rated the provided postnatal care and their relationship with the personnel as good or excellent. The mean total scores of the mothers' perceptions were not different based on their satisfaction with postnatal care (P=0.646) and time of the first referral after birth (P=0.251), but they were significantly different according to the number of referrals (P=0.023) and their satisfaction with the health personnel (p <0.001). Conclusion: The study results revealed that mothers had a good perception about postnatal care provided by health center staff. Hence, it is necessary to educate all health staff in this regard to provide high-quality postnatal care to all mothers who refer to these centers.